February Editorial (Journal of Parents and Teachers, 2012)
This editorial presents a number of Padres y Maestros focused on emotional education as a key factor to fully develop people. It includes articles about emotional education, mediation, values, coexistence and social competence.
Keywords: Emotional education; integral development; body and mind; values; communication; society; emotional competence.